Evaluation of physical traits and chemical components associated with hard-to-cook phenomenon in Bambara groundnut (Vigna subterranea (L.) Verdc.) - Tan, Xin Lin (2023)
Bambara groundnut (Vigna subterranea (L.) Verdc.) is a potential crop for future sustainable agri-food systems. However, utilisation of the crop is constrained by several factors, one of which is the hard-to-cook (HTC) phenomenon. The HTC seeds do not soften sufficiently after prolonged cooking time, thus demanding more energy for preparation. This, in turn, reduces the economic value and consumers acceptance of the pulse. The objective of this project was to explore the HTC traits in Bambara groundnut through the evaluation of physicochemical, microstructural, and technological properties to provide a basis to improve the processing efficiency and utilisation of the nutrient-dense pulse.